INNOVATIVE TECHNOLOGIES FOR DECORATING LIGHT INDUSTRY PRODUCTS - KULESHOVA, Svitlana; KOSHEVKO, Julia; NAJCHUK, Diana; LEBEDYNSKA, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to the solution of the task of forming project images in modern mass fashion in the context of the use of innovative decoration technologies on the example of designing an author's collection of women's clothing.The scientific novelty of the study consists of the analysis and systematization of creative and innovative decoration technologies with the aim of further integration into the fashion design of clothing. The study's practical significance lies in the study of characteristic techniques and elements of innovative clothing decoration. The article describes the stages and provides recommendations for producing the author's prints for decorating products of the author's collection. The authors focused on developing the author's print using computer technologies in universal graphic reactors of both raster and vector graphics for further thermal transfer printing.The study demonstrates the process of forming a sketch of a fashionable design image using an information model, which allows authors to present it as a single symbolic system using modern practices of visual presentation of trendy innovations.The products in the collection are made of different materials, which, when combined into sets, give the image of unusualness and sophistication. The collection was developed in the format of the Pop Art style using fashion trends. The authors defined and thought out the main images, forms, and constituent elements of the designed products of the author's collection sets. When creating clothing models, special attention was paid to the originality and multifunctionality of the collection's products and their parts. The creative and design, constructive, and technological solutions of models of sets of the author's collection were produced and presented at the All-Ukrainian competition of young designers "Colours of Podillia" (Khmelnytskyi, KhNU, 2022), were developed.
Keywords: innovative technologies; decoration; author's collection; print; project image